The Role of Prosecutor in Criminal Procedure of Vietnam and Japan - Yen, Nguyen Hai (VNU Journal of Science: Legal Studies; Vol 36 No 1DO - 10.25073/2588-1167/vnuls.4191, 2020)
This article discusses the differences between the prosecutors in the criminal system of Vietnam and Japan in the enforcement of the prosecution right and the activities in the process of resolving criminal cases. At the same time, the cause of the legal history, as well as the organizational model between the two criminal justice systems that led to the differences of these two subjects of the two systems is also mentioned. The article aims to contribute to comparative research between Vietnam and Japan in the field of criminal procedure law and play as reference material in the research and learning process. Keywords: Prosecutor, criminal procedure, Japan. References: [1] Trường Đại học Kiểm sát Hà Nội, Mô hình tố tụng hình sự Nhật Bản, <http://tks.edu.vn/thong-tin-khoa-hoc/chi-tiet/79/146> [2] J. Mark Ramseyer and Eric B. Rasmusen, Why Is the Japanese Conviction Rate so High?, The Journal of Legal Studies 30, 1(2001) 53 [3] Supreme Court of Japan, Outline of Criminal Justice in Japan 2016, Table 4, <http://www.courts.go.jp/english/vcms_lf/Outline_of_Criminal_Justice_in_Japan_2016.pdf, truy cập 25/12/2017>. [4] Shigemitsu Dando, System of Discretionary Prosecution in Japan, The American Journal of Comparative Law, 18 (1970) 3 [5] A Didrick Castberg, Prosecutorial Independence in Japan, Crime and Justice, 41 (2012) 19. [6] Trường Đại học Kiểm sát Hà Nội, Bàn về vai trò, trách nhiệm của Kiểm sát viên trong tố tụng hình sự, <http://tks.edu.vn/thong-tin-khoa-hoc/chi-tiet/79/750> [7] Phạm Văn An, Nâng cao vai trò, trách nhiệm, tính chủ động của Kiểm sát viên trong thực hành quyền công tố và kiểm sát xét xử vụ án hình sự, Tạp chí kiểm sát, 15 (2015) 34 [8] Malcolm Feeley and Setsuo Miyazawa, The Japanese Adversary System in Context: Controversies and Comparisons, Advances in Political Science, Houndsmills, Basingstoke, Hampshire; New York, Palgrave Macmillian, 2002 [9] UNAFEI, “The Criminal Justice System in Japan: Prosecution” n.d., p. 43 <http://www.unafei.or.jp/english/pdf/RS_No53/No53_10FP.pdf>. [10] Stéphanie Balme and Mark Sidel, Vietnam’s New Order: International Perspectives on the State and Reform in Vietnam, Palgrave Macmillan, 2007 [11] Trường Đại học Kiểm sát Hà Nội, Tổng quan về hệ thống pháp luật các nước ASEAN, <http://tks.edu.vn/thong-tin-khoa-hoc/chi-tiet/120/258> [12] Lê Hữu Thể, Nguyễn Thị Thuỷ, Hoàn thiện mô hình tố tụng hình sự Việt Nam theo yêu cầu cải cách tư pháp, <http://tks.edu.vn/thong-tin-khoa-hoc/chi-tiet/79/28> [13] Đào Trí Úc, Tổng quan về mô hình Tố tụng hình sự Việt Nam, thực trạng và phương hướng hoàn thiện, <http://tks.edu.vn/thong-tin-khoa-hoc/chi-tiet/79/32> [14] Marcia E. Goodman, The exercise and Control of Prosecutorial Discretion in Japan, Pacific Basin Law Journal, 5 (1986) 78.